A fatigue failure formula and a new measure of the roughness of a terrain profile. (1st January 2014) - Sun, T.C.; Gorsich, D.; Chaika, M.; Wei, Jinfeng; Qiu, S.; Alyass, K.
There have been complaints that the root mean square (RMS) does not describe the roughness of terrain profiles well. Similar complaints can be made about the international roughness index (IRI) as a measurement of roughness of terrain profiles. In this paper, by using the rainflow count of the oscillations of the terrain profiles, we shall first propose a fatigue failure formula and then we shall modify it to define a new measure of roughness of terrain profiles. We shall show that this new measure can describe the roughness better than the RMS and the IRI and hence, can be used, either independently or in conjunction with RMS and IRI, as a new measure of roughness of terrain profiles.